Cocrystallization of Febuxostat with Pyridine Coformers: Crystal Structural and Physicochemical Properties Analysis - Lei Gao; Xianrui Zhang (Journal of Chemistry)
Drug cocrystals and salts have promising applications for modulating the physicochemical properties and solubility of pharmaceuticals. In this study, a cocrystal and two salts of febuxostat (FEB) with pyridine nitrogen coformers, including 4, 4′-bipyridine (BIP), 3-aminopyridine (3AP) and 4-hydroxypyridine (4HP), were designed to improve the solubility of FEB. The single-crystal structures were elucidated, and their physical and chemical properties were investigated by IR, PXRD, and DSC. In addition, drug-related properties, including the solubility and powder dissolution rate were assessed. The solubility and powder dissolution studies showed that the FEB-BIP cocrystal and FEB-3AP salt have superior dissolution compared to FEB.